Phosphoglycerate Kinase Is Involved in Carbohydrate Utilization, Extracellular Polysaccharide Biosynthesis, and Cell Motility of Xanthomonas axonopodis pv. glycines Independent of Clp - Guo, Wei; Gao, Jie; Wang, Hong-Jie; Su, Ru-Yi; Sun, Chu-Yun; Gao, Si-Han; Liu, Jian-Zhong; Chen, Gong-You (Frontiers in Microbiology, 2020)
Phosphoglycerate kinase (Pgk), catalyzing the reversible conversions between glycerate-1.3-2P and glycerate-3P, plays an important role in carbohydrate metabolism. Here, we show that a Pgk-deficient mutant (NΔpgk) of Xanthomonas axonopodis pv. glycines (Xag) could grow in medium with glucose, galactose, fructose, mannose, or sucrose, as the sole carbon source, suggesting that Xag may employ Entner-Doudoroff and pentose phosphate pathway, but not glycolysis, to catabolize glucose. NΔpgk could not utilize pyruvate, suggesting that Pgk might be essential for gluconeogenesis. Mutation in pgk led to a reduction of extracellular polysaccharide (EPS) biosynthesis, cell motility, and intracellular ATP. As a result, the virulence of NΔpgk was significantly compromised in soybean. NΔpgk could be fully complemented by the wild-type pgk, but not by clp (encoding Crp-like protein). qRT-PCR analyses demonstrated that pgk is regulated by the HrpG/HrpX cascade, but not by Clp. These results suggest that Pgk is involved in carbohydrate utilization, EPS biosynthesis, and cell motility of Xag independent of Clp.